Evaluation of properties of cold in place recycling material : a case study - Jhatial, Irfan Khan (2006)
Cold in place recycling (CIPR) has gained popularity in Asian countries because it is easy, environment friendly and cost effective. Since it is a relatively new technology therefore there is a need to revise standards and widen research on its properties. The main purpose of the study is to investigate the properties of cold in place recycling material obtained from a study site near Malacca. The study also aims to predict the life of newly recycled pavement using computer software WESLEA 3.0 in terms of rutting and fatigue failures. The results obtained for pavement life are in terms of application of standard single axle. Since cement is used as stabilizer in the study site’s recycling method, three cement contents were chosen to evaluate properties of CIPR material i.e. 2%, 4% and 6%. Laboratory investigation included determination of maximum dry densities by varying water contents with different cement contents, dry sieve analysis and compressive strength tests. Optimum water contents obtained from dry density tests were used to make compressive strength test samples. Two curing durations were chosen, 7 days and 28 days to develop the strength of samples. The samples were made using 100 mm cube mould. Two samples of same parameters were made for both dry density and cube tests to get an average result. The findings of this study also showed that 50% increase of cement by weight can double the cube compressive strength of 7 days cured samples. Experimental investigations showed that there was slight increase in dry density with increase of cement content. 2% cement content was found to be inappropriate to use because of very low strength. Analysis of WESLEA 3.0 showed that increasing the cement can significantly improve pavement performance for rutting failures. From compressive strength perspective 6% cement content is recommended by this research.